Analysis Of Efficiency Of Rice Farming Production Factors In Village New Kecamatan Batang Kuis Deli Serdang District - Henny Wahyuni; Adriansyah Adriansyah; Lisdayani Lisdayani; Putri Mustika Sari (JASc (Journal of Agribusiness Sciences), 2019)
The government of North Sumatra is trying to increase the production and productivity of rice commodities. The level of income derived from rice farming is often lower when compared to planting horticultural products or other agricultural commodities. The level of income derived from rice farming is often lower when compared to planting horticultural products or other agricultural commodities. Basically, rice farming has two factors that will affect the production process, namely internal land use, labor and capital factors and external factors which include factors of production that cannot be controlled by farmers such as climate, weather, price changes and so on. North Sumatra Province began to develop organic agriculture, especially for rice plants to reduce farmers' dependence on chemical pesticides and fertilizers. The purpose of this study is to analyze the factors of production that affect rice farming, and to analyze the level of efficiency of the use of production factors in rice farming in the new village of quiz stem sub-district. The method used in the research in descriptive method is sampling and interviews with farmers in the new village of Kec. Batang quiz. The parameters observed include the analysis of production factors and the analysis of the efficiency of the use of production factors. The results obtained from the study that most farmers in the new village are high school graduates and all the factors of production have a very significant effect on rice farming in the new village. And the variable seed, chemical fertilizer, organic fertilizer, land area and labor very significantly affect production. In the future it is expected that rice farmers in the new village can minimize the use of seeds, chemical fertilizers and pesticides so that optimal rice production is obtained.